Homenagem à Professora Sonia Ranincheski - Prestes, Anita Leocadia; Neves, Abilio Afonso Baeta; McManus, Concepta; Schmidt, Benício V.; Maybury-Lewis, Biorn; Sena, Caridad Massón; Negri, Camilo; Busnello, Flávio Marcelo; Ávila, Nuria Rodríguez; CESPRI, Equipe; Sobral, Fernanda A. da Fonseca; Batallion, Gilles; et al. (Revista Debates, 2020)
Textos de Homenagem à professora Sonia Ranincheski